Signal transducer and activator of transcription-3 licenses Toll-like receptor 4-dependent interleukin (IL)-6 and IL-8 production via IL-6 receptor-positive feedback in endometrial cells - Cathy Thornton (Mucosal Immunology, 2016)
Interleukin 6 (IL-6), acting via the IL-6 receptor (IL6R) and signal transducer and activator of transcription-3 (STAT3), limits neutrophil recruitment once bacterial infections are resolved. Bovine endometritis is an exemplar mucosal disease, characterized by sustained neutrophil infiltration and elevated IL-6 and IL-8, a neutrophil chemoattractant, following postpartum Gram-negative bacterial infection. The present study examined the impact of the IL6R/STAT3 signaling pathway on IL-8 production by primary endometrial cells in response to short- or long-term exposure to lipopolysaccharide (LPS) from Gram-negative bacteria. Tyrosine phosphorylation of STAT3 is required for DNA binding and expression of specific targets genes. Immunoblotting indicated constitutive tyrosine phosphorylation of STAT3 in endometrial cells was impeded by acute exposure to LPS. After 24 h exposure to LPS, STAT3 returned to a tyrosine phosphorylated state, indicating cross-talk between the Toll-like receptor 4 (TLR4) and the IL6R/STAT3 signaling pathways. This was confirmed by short interfering RNA targeting the IL6R, which abrogated the accumulation of IL-6 and IL-8, induced by LPS. Furthermore, there was a differential endometrial cell response, as the accumulation of IL-6 and IL-8 was dependent on STAT3, suppressor of cytokine signaling 3, and Src kinase signaling in stromal cells, but not epithelial cells. In conclusion, positive feedback through the IL6R amplifies LPS-induced IL-6 and IL-8 production in the endometrium. These findings provide a mechanistic insight into how elevated IL-6 concentrations in the postpartum endometrium during bacterial infection leads to marked and sustained neutrophil infiltration.